PENGARUH MOTIVASI WISATAWAN, DAYA TARIK WISATA DAN CITRA DESTINASI TERHADAP MINAT BERKUNJUNG WISATAWAN KE WISATA RELIGI MAKAM SYEKH BURHANUDDIN - Warman, Bramadhan Putra; Zulvianti, Nora; Putri, Hesti Mari (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study has been initiated due to the declining interest of visitors in visiting the tomb of Sheikh Burhanuddin in Padang Pariaman Regency. The government is deeply concerned about managing this religious tourism site, given its historical significance as the final resting place of a prominent figure who played a key role in spreading Islam in West Sumatra. Moreover, this tomb holds cultural heritage status, making it a valuable asset for both tourism and educational purposes. The research employs a descriptive quantitative approach to analyze the factors affecting visitors' interest in the tomb of Sheikh Burhanuddin. The sample size comprises 230 respondents selected through accidental sampling. Data analysis is conducted using Structural Equation Modeling Partial Least Squares (SEM PLS). The findings indicate that while tourist motivation has a positive impact on visiting interest, it is not statistically significant. On the other hand, tourist attraction and destination image both have a positive and significant influence on visitors' interest in the tomb. Furthermore, the combined analysis reveals that tourist motivation, tourist attraction, and destination image collectively exert a positive and significant impact on visitors' interest in religious tourism at the tomb of Sheikh Burhanuddin.